2017
DOI: 10.1002/pros.23429
|View full text |Cite
|
Sign up to set email alerts
|

Sexual steroids in serum and prostatic tissue of human non‐cancerous prostate (STERPROSER trial)

Abstract: STERPROSER trial provides evidence for higher DHT concentration in highvolume prostates, that could reflect either higher 5-alpha reductase expression or lower expression of downstream metabolizing enzymes such as 3a-hydoxysteroid dehydrogenase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Despite the apparent lack of an appreciable effect of HSD3B1 genotype on circulating steroid levels, clear phenotypes with HSD3B1 genotype have been observed in two asthma cohorts 21 and at least eight prostate cancer cohorts 49 , suggesting that the effects of HSD3B1 genotype are mediated largely independent of circulating sex steroid levels. Steroid levels in tissues can differ profoundly from those in circulation [50][51][52] , so HSD3B1 genotype could potentially affect concentrations at the cell or tissue level without measurably affecting concentrations in circulation, which should be further studied. Other measures such as circulating cortisol levels and inflammatory cytokines are also important to analyze, but these data were not available in the UK Biobank.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the apparent lack of an appreciable effect of HSD3B1 genotype on circulating steroid levels, clear phenotypes with HSD3B1 genotype have been observed in two asthma cohorts 21 and at least eight prostate cancer cohorts 49 , suggesting that the effects of HSD3B1 genotype are mediated largely independent of circulating sex steroid levels. Steroid levels in tissues can differ profoundly from those in circulation [50][51][52] , so HSD3B1 genotype could potentially affect concentrations at the cell or tissue level without measurably affecting concentrations in circulation, which should be further studied. Other measures such as circulating cortisol levels and inflammatory cytokines are also important to analyze, but these data were not available in the UK Biobank.…”
Section: Discussionmentioning
confidence: 99%
“…Others have reported comparisons of serum and tissue concentrations for certain steroids and tissues with varying results. For example, two different groups [39, 40] reported elevated concentrations of DHEA and DHT in prostate tissue compared to serum, but testosterone concentrations that were greater in serum than in tissue. In vivo steroid concentration ratios are affected by factors other than cells’ tendency to take up steroids, including metabolism that occurs within cells; the depressed testosterone concentrations in prostate tissue could reflect its conversion to DHT by enzyme 5α-reductase [41].…”
Section: Discussionmentioning
confidence: 99%
“…Sex steroid levels in serum and prostate tissue were recently accurately characterized in men without PCa (Neuzillet et al 2017). Comparing the differences in serum and tissue sex steroids between smaller prostates (<50 g) and those affected by BPH (>50 g), the authors found intraprostatic DHT levels correlate with prostate size.…”
Section: Changes In Sex Steroids During Prostate Cancer Progression Pmentioning
confidence: 99%
“…The relationship between circulating and prostate tissue levels of androgens has been addressed in several studies (Bartsch et al 1986, Miyoshi et al 2014, Cook et al 2017, Neuzillet et al 2017. Overall, intraprostatic levels of DHT and testosterone, as well as dehydroepiandrosterone (DHEA) and androgen metabolites such as androstane-3β,17βdiol (3β-diol) are 5-to 10-fold higher in prostate tissue than those in the serum.…”
Section: Relationship Between Serum and Prostate Tissue Sex Steroid Lmentioning
confidence: 99%